2022
DOI: 10.3390/lubricants10120347
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Computational Fluid Dynamics of Rotary Shaft Seals

Abstract: The primary task of rotary shaft seals is to prevent an unwanted fluid transfer between two areas. In shaft passages of gearboxes, for example, rotary shaft seals avoid the leakage of transmission oil to ambient air. This means the flow in the lubricant film in the sealing gap between the sealing edge and the shaft surface consists of at least two phases. Taking the phenomenon of cavitation into account, the flow consists of three phases. This study aims to provide an in-depth understanding of the multiphase f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…according to [15]. The measured values were then fitted to the curve described by Equation ( 18) in order to determine the parameters a 1 , b 0 , b 1 and b 2 .…”
Section: Boundary and Initial Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…according to [15]. The measured values were then fitted to the curve described by Equation ( 18) in order to determine the parameters a 1 , b 0 , b 1 and b 2 .…”
Section: Boundary and Initial Conditionsmentioning
confidence: 99%
“…Thus, there is no fixed boundary between the fluid to be sealed, the oil, and the surrounding fluid, the air. For the prediction of, for example, cavitation zones in the sealing gap, this multiphase flow has already been successfully simulated in the past [14,15]. Finite element analysis (FEA) of a rotary shaft seal has already been used to analyze the radial deformation and contact pressure distribution [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the calculation of leakage without considering structural thermal deformation can lead to significant error [9][10][11]. Other researchers also investigated the performance of a mechanical seal considering structural thermal deformation to accurately calculate the leakage rate of the seals in mechanical devices [12][13][14].…”
Section: Introductionmentioning
confidence: 99%